2018
DOI: 10.1108/ijmpb-01-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Programming for holistic value creation: collaboration, coordination and perception

Abstract: Purpose The purpose of this paper is to holistically explore value creation approaches in a program of cultural projects to inform the practices of project/program management in both public and private sectors. Design/methodology/approach The paper brings together the literature on project, program and portfolio value creation to inform a case study conducted with engaged scholarship research methods. Findings Three themes of value creation are revealed: managing collaboration, coordination and perception.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…, 2017; Lappi et al. , 2019; Laursen and Killen, 2019; Nogeste, 2010; Veiga and Franco, 2015; Zhu et al. , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2017; Lappi et al. , 2019; Laursen and Killen, 2019; Nogeste, 2010; Veiga and Franco, 2015; Zhu et al. , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, the CURV has been handled individually or sometimes as subsets (Martinsuo, 2020;Teller et al, 2014;Williams, 2017). and Killen, 2019;Nogeste, 2010;Veiga and Franco, 2015;Zhu et al, 2020). Many aspects of PMI are impacted not only by cultural differences and sociocultural status (Sales et al, 2022;Schlindwein and Geppert, 2020) but also by the emotional dimensions of managers and employees, which play a crucial role in the process (Fiorentino and Garzella, 2015;Al Hosani et al, 2020;Khan et al, 2020;Kroon and Noorderhaven, 2018;Kroon and Reif, 2023;Safavi, 2021;Thelisson and Meier, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of knowledge and innovation management (C11) has been highlighted by several authors (Rijke et al, 2014;Laursen, Killen, 2019). Pellegrinelli et al (2015) observed that when a program is not only a coordinating tool for independent projects, but also an organizational mechanism for achieving the main strategic goal or change, its component projects should be managed with utmost care to ensure efficient implementation and utilization of existing knowledge.…”
Section: Rq1 What Are the Specific Areas That Contribute To The Succe...mentioning
confidence: 99%
“…Managing value creation in portfolios appears to be a fruitful path for PPM research (Laursen & Svejvig, 2016), as the notion of PPM value and success has gradually changed focus from being project- and product-centric toward being value-centric (Ang & Biesenthal, 2017). As we expand our understanding of value and success (Laursen & Killen, 2019), we become better at assisting organizations in establishing a more strategic orientation to their external and internal organizational environments (Martinsuo & Geraldi, 2020).…”
Section: Introductionmentioning
confidence: 99%